Regulatory disempowerment: How enabling and controlling forms of power obstruct citizen‐based regulation. Issue 3 (18th June 2020) - Gray, Garry; van Rooij, Benjamin
Abstract: Regulatory studies assume that citizens can act as regulators to complement or correct failing state and market forms of regulation. Yet, there is a growing literature that shows that in reality citizens may fail to be effective regulators. This paper systematically analyses how power inequalities obstruct citizens in their regulatory roles. It compares four case studies with highly different social and political contexts but with similar outcomes of citizens failing to regulate risk. The case studies are analyzed by operationalizing sociological and political science ideas about manifestations of enabling and controlling forms of power in order to understand the way power inequalities obstruct citizens in their regulatory roles across diverse contexts. The article shows how citizens, from farmers and manual workers in both authoritarian developing and democratic developed contexts to even highly trained medical professionals from the US, have limited agency and are disempowered to act as regulators. Our analysis reveals that five patterns of disempowerment play a crucial role in obstructing successful society‐based regulation: (i) dependency, (ii) capacity, (iii) social hierarchy, (iv) discursive framing, and (v) perverse effects of legal rights.